Analisis Key Performance Indicator (KPI) Dan Pengetahuan Produk Syariah Terhadap Kinerja Tenaga Penjualan Dengan Motivasi Kerja Sebagai Variabel Intervening Pada Bank Muamalat Indonesia (BMI) - Chaerudin, Chaerudin; Pakkanna, Mukhaer (Journal of Education on Social Science (JESS), 2023)
The growth of Islamic banking is influenced by various factor, including the performance of sales personnel in offering products. Selling skills should also be supported by a deep product knowledge product sharia. In addition, work motivation is an integral part of performance enhancement. The use of Key Performance Indicator (KPIs), Products Knowledge, and work motivation and their relationship with performance need to be measured to what extent these variables are interconnected. This research aims to analyze Key Performance Indicators and Sharia Product Knowledge on the performance sales personnel, with work motivation as an intervening at Bank Muamalat Indonesia. The background of the study is based on understanding how Key Performance Indicators and Knowledge Product Sharia owned by sales personnel can explain the relationship with performance, with work as mediation. This research is a quantitative study and utilizes a questionnaire distributed to sales force or marketing employees. Data collection was done by distributing the questionnaire through online media to the sales force. The data processing and analysis software used is SMARTPLS 3.0. The results of the direct effect variable test show that the Key Performance Indicator (X1) has a significant effect on Sales Force Performance (Z) at 0.192 with a t-statistic (2.444>1.96) or p-value (0.015<0.05). The effect of Key Performance Indicator (X1) on Work Motivation (Y) is a significant at 0.291 with a t-statistic (3.525>1.96) or p-value (0.000<0.05). The effect of Work Motivation (Y) on Sales Force Performance (Z) is significant at 0.366 with t-statistic (4.581>1.96) or p-value (0.000<0.05). The effect Knowledge Product sharia (X2) on Sales Force Performance (Z) is significant at 0.241 with a t-statistic (2.652>1.96) or p-value (0.008<0.05). The Effect of Knowledge Products Sharia (X2) on Work Motivation (Y) is significant at 0,453 with a t-statistic (5.542>1.96) or p-value (0.000<0.050). Meanwhile, for the indirect effect analysis, the indirect effect of Key Performance Indicator (X1) on Sales Force Performance (Z) through Work Motivation (Y) is 0.106 with p-value of 0.012 <0.05, which means that Work Motivation (Y) mediates the effect of Key Performance Indicator (X1) on Sales Force Performance (Z). The indirect effect of Knowledge Product Sharia (X2) on Sales Force Performance (Z) through Work Motivation (Y) is 0.166 with p-value of 0.001 <0.05, which means that Work Motivation (Y) mediates the effect Knowledge Product Sharia (X2) on Sales Force Performance (Z).